On Integrating Multiple Restriction Domains to Automatically Generate Test Cases of Model Transformations - Nguyen, Hanh Thi; Dang, Hanh Duc (Informatica, 2023)
Testing model transformations poses several challenges, one of which is how to automatically generate effective test suites. Existing approaches in the literature often focus on exploiting either structural aspects of models captured by a metamodel or restrictions as contracts within the specification of model transformation for a partition analysis to generate test suites. However, test cases for model transformation, i.e., test models, often need to be defined not only from one restriction source as within the current methods but also from many different sources. This paper introduces a method to facilitate defining test models on such multiple restriction domains. This method also allows the tester to flexibly select and combine constraints as a restriction on test models for different strategies and objectives of the model transformation testing. We develop a support tool based on the OCL tool USE and perform experiments on several different transformations to point out the effectiveness of our method.